Circulation of thermophilic Campylobacter in pigeons, turkeys, and humans at live bird markets in Egypt - Sayed, Amal S. M.; Ibrahim, Ahmed I.; Sobhy, Mona M.; Elmahallawy, Ehab Kotb; Alsowayeh, Noorah; Alarjani, Khaloud Mohammed; El-khadragy, Manal F.; Youseef, Asmaa Gahlan (Frontiers in Veterinary Science, 2023)
Live bird markets increase the risk of transmission of zoonotic diseases. Few studies have investigated the potential zoonotic transmission of Campylobacter in Egypt. Therefore, our study was carried out to investigate the presence of Campylobacter species, mainly Campylobacter jejuni (C. jejuni) and Campylobacter coli (C. coli), in pigeons and turkeys sold at poultry shops. Furthermore, the study aimed to explore the potential occupational risk of Campylobacter infection, mainly among workers at poultry shops. Six hundred (n=600) samples from various organs were obtained from pigeons and turkeys from live bird shops in the Giza and Asyut provinces in Egypt. Additionally, one hundred stool samples were collected from persons working at poultry shops. Circulation of thermophilic Campylobacter in pigeons, turkeys, and humans was investigated based on culture and molecular methods. The rate of detection of Campylobacter species from the samples was significant when the culture method was used alone in comparison to when it was used in combination with mPCR. The prevalence rates of Campylobacter species detected by mPCR were 36% (C. jejuni 20%; C. coli 16%), 28% (C. jejuni 12%; C. coli16%), and 29% (C. jejuni 15%; C. coli 14%) in pigeons, turkeys, and workers, respectively. In pigeons, significant variations in the C. jejuni and C. coli occurrence rates were reported in terms of the intestinal content (15%, 4%), liver (4%, 13%), and skin (9%, 7%), respectively. In turkeys, Campylobacter species were mostly detected in liver samples with a percentage of 19%, followed by the skin (12%), and the intestinal content (8%). In conclusion, Campylobacter species are circulating in poultry farms in Egypt and could represent a hazard for humans. It is recommended that biosecurity measures should be applied to mitigate the occurrence of Campylobacter in poultry farms. Moreover, there is an urgent need to transform live bird markets into chilled poultry markets.